Volatile organic compounds of plants induced by insects: current situation in Mexico - Cantúa Ayala, Jesús Antonio; Flores Olivas, Alberto; Valenzuela Soto, José Humberto (Revista Mexicana de Ciencias Agrícolas, 2019)
Plants produce and emit volatile organic compounds, generally they are mixtures that are composed of terpenes, fatty acid derivatives and aromatic compounds. Volatile organic compounds serve plants for: reproduction, attracting pollinators or seed dispersers, as a defense to repel insects or stop colonization by phytopathogenic bacteria and fungi, to attract natural enemies of herbivores and as intraspecific and interspecific messengers. Plants emit some volatiles especially when the vegetative parts are exposed to abiotic or biotic stimulation. Considering the foregoing, a bibliographic review was carried out, the purpose of which is to present the classification of volatile organic compounds in plants, to describe and indicate the characteristics of the extraction and identification techniques of volatile organic compounds, to present the advances reported in the scientific literature about these compounds induced by insects and their current situation in Mexico.